Enhanced cartilage repair in 'healer' mice—New leads in the search for better clinical options for cartilage repair. (February 2017) - Fitzgerald, Jamie
Abstract: Adult articular cartilage has a poor capacity to undergo intrinsic repair. Current strategies for the repair of large cartilage defects are generally unsatisfactory because the restored cartilage does not have the same resistance to biomechanical loading as authentic articular cartilage and degrades over time. Recently, an exciting new research direction, focused on intrinsic cartilage regeneration rather than fibrous repair by external means, has emerged. This review explores the new findings in this rapidly moving field as they relate to the clinical goal of restoration of structurally robust, stable and non-fibrous articular cartilage following injury.